Taḥlīlu al Syakhṣiyyāti al Ra’īsiyyati fī Riwāyati Alliṣu wal Kilābi li Najībi Mahfūẓ (Dirāsatun Taḥlīliyyatun fī al Naqdi al Adabiy) - Juliyah, Juliyah; Daud, Izzat Muhammad (Al-Uslub: Journal of Arabic Linguistic and Literature, 2021)
This study aims to convey certain goals to the reader. Aim These are in the form of moral values, social values, and religious values. About the main character in the novel allishu walkilab by Najib Mahfuz in the study of literary criticism, there are several values which describes the behavior or character of the main character who takes revenge for being betrayed. This research uses qualitative research by using descriptive approach because the author uses theory in the study of literary criticism to analyzing describe the values ​​contained in the main character. The object that studied in this study are the main characters in the novel Allishu Walkilab by Najib Mahfuz studies literary criticism with a pragmatic approach in which this novel is used as a source data in research. The results of this study are aimed at the reader, namely the usefulness effect for readers using a pragmatic approach. the values ​​contained in the character in the novel allishuwalkilab by Najib Mahfuz. the author took some excerpts of text that have several values, namely moral values ​​18, social values ​​5, religious values ​​2